SOME RECOMMENDATIONS CONCERNING THE MEDICAL-PSYCHOLOGICAL POSTISOLATIONAL ASSISTANCE AND SUPPORT OF SERVICEMEN, THAT ENDURED TORTURE IN THE COURSE OF IMPRISIONMENT - Shyrobokov, J.; Timchenko, O.; Kravchenko, K. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The issue of medical-psychological assistance and support to individuals, that have been imprisoned and/or tortured is an up-to-date issue for many countries in the world. In accordance with the data provided by Amnesty International people are undergoing torture and cruel treatment at least in 140 countries of the world. In 2014 this issue has become extremely urgent, due to the fact that the armed conflict within a country always negatively influences the adherence of human rights. The definition of captivity has been actualized in 2014, in the course of the Maidan protests and received its continuity as a result of the situation that occurred in Crimea and the East of the Luhansk and Donetsk regions. Tortures and cruel treatment are prohibited by international law. There’s an international consensus with regard to the fact that such abuses violate the dignity of a human being and cannot be justified by any circumstances. But, most unfortunately the realities of today and the conduct of combat activities in the East of Ukraine force us to make conclusions about the non-adherence of the aggressorstate to the Geneva conventions and the humane treatment of prisoners of war. Thus, the attention of scientists has been directed solely at solving these issues and providing certain recommendation concerning the medicalpsychological post-isolation assistance and support to military personnel, who have endured torture in captivity. The material of the article is based on conducted empirical research and the experience of providing psychological assistance to the prisoners of war in the course of the post-isolation period. The overall amount of prisoners of war that have participated in the research are 694, who have been deliberated from captivity in the course of the years 2015-2019. From the general amount of people under research (n=694), 643 individuals (92,7%) – are military men of the Armed Forces of Ukraine and 51 individual (7,3%) – are the combatants of volunteer battalions (representatives of volunteer battalions). The articles presents the peculiarities of psychological work with former prisoners, the peculiarities of every stage of providing psychological assistance to military men has been scrutinized. There’s also the presented analyses of negative psychological implications of being held in captivity, among which the sense of guilt and shame, the control of ones’ emotions, avoiding communication and isolation, misfortunes in terms of marriage and family relations, aggressive reactions and the yearning for vengeance.